A physiological signal based approach on stress assessment through emotion, physical, and cognitive stimuli: A theoretical frame work - Murugappan, M., Dr.; Karthikeyan, P.; Bong, Siao Zheng; Ku Nor Syamimi, Ku Ismail; Sazali, Yaacob, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.